UV‐Selective Optically Transparent Zn(O, S)‐Based Solar Cells. Issue 11 (6th November 2020) - Lopez-Garcia, Alex J.; Bauer, Andreas; Fonoll Rubio, Robert; Payno, David; Jehl Li-Kao, Zacharie; Kazim, Samrana; Hariskos, Dimitrios; Izquierdo-Roca, Victor; Saucedo, Edgardo; Pérez-Rodríguez, Alejandro
Abstract : Transparent Photovoltaics In article number 2000470, Alex J. Lopez‐Garcia and co‐workers report on the fabrication of transparent UV‐selective solar cells based on Zn(O, S) as the absorber. The use of Zn(O, S) as UV‐harvesting material is discussed, and a record device is presented showing a power conversion efficiency of 0.5% at an average visible transmittance of 69% with a device that includes C60 as electron transport layer.